Using population viability analysis for management recommendations of the endangered endemic peninsular pronghorn - Cancino, Jorge; Rodríguez-Estrella, Ricardo; Miller, Philip (Instituto de Ecología, A.C., 2010)
A case study on the viability of small populations with a restricted distribution and reduction in habitat quality is addressed using the peninsular pronghorn (Antilocapra americana peninsularis) of Baja California Peninsula, Mexico. The present size of its wild population is less than 250 individuals, being in an IUCN Critically Endangered status. Captive management of peninsular pronghorn began in 1998 in El Vizcaino Desert with 22 founders. We predicted future trends in the pronghorn population, and assessed the risk of extinction through population viability analysis (PVA) using VORTEX. Deterministic and stochastic factors designed to simulate human activity on the landscape were evaluated for their impact on this endemic taxon. The concept of supportive breeding was assessed. The results of PVA simulations indicate that removal of founder animals to initiate the captive breeding did not significantly reduce the viability of the wild population. However, a population size <100 individuals greatly increase the risk of extinction. Also, one of the most important factors for the viability of the peninsular pronghorn population is the survival of fawns. The risk of extinction can be significantly reduced using supportive breeding. We propose that the likelihood of successful population management of peninsular pronghorn could be increased establishing a number of subpopulations across the species’ historic range and, even more importantly, the establishment of ecologically functional connections between these subpopulations to create a proper metapopulation. Captive breeding can be an important factor to decrease the probability of extinction of this subspecies. Key Words: Antilocapra americana, endangered, management, PVA, recovery.